FAKTOR – FAKTOR YANG MEMPENGARUHI STOCK MARKET RETURN - Shine, Angel Elaine; Rasyid, Rosmita (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This study aims to examine the effect of exchange rates, trading volume activity and COVID-19 on stock market returns in publicly listed companies engaged in the consumer non-cyclicals and listed on the Indonesia Stock Exchange (IDX) in 2020-2021. This study used a purposive sampling method and company data that matched the criteria were found 61 companies. Data processing uses the Microsoft Excel 2021 and SPSS Statics programs. From this study it can be concluded that exchange rate activity, trading volume activity and COVID-19 using daily positive cases have an effect on stock market returns.